2019
DOI: 10.1111/asj.13181
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation quality and aerobic stability of mulberry silage prepared with lactic acid bacteria and propionic acid

Abstract: The objective of this study was to examine the fermentation quality and aerobic stability of mulberry (Morus alba L.) silage prepared with lactic acid bacteria (LAB) and propionic acid (PA). The selected LAB strains Lactobacillus (L.) plantarum LC365281 (L1) and L. brevis LC365282 (L2), and commercial inoculant strains L. plantarum Gaofuji (GF) and L. buchneri Fresh (FR), and PA were used as additives for silage preparation. Silage treatments were designed as control, L1, L2, GF, FR, PA, PA + L1, PA + L2, PA +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
3
20
0
1
Order By: Relevance
“…These observations suggested that, compared with epiphytic LAB, Lactobacillus plantarum has a higher ability to thrive in high DM silage. In the experiment, despite mulberry leaves being wilted for only 6 h, a relatively higher DM (38.5% vs 21.5% DM) content was obtained as compared with that in study of Zhang et al [9]. This high DM may depress the activity of epiphytic LAB, which explained the poor fermentation quality of control silage.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…These observations suggested that, compared with epiphytic LAB, Lactobacillus plantarum has a higher ability to thrive in high DM silage. In the experiment, despite mulberry leaves being wilted for only 6 h, a relatively higher DM (38.5% vs 21.5% DM) content was obtained as compared with that in study of Zhang et al [9]. This high DM may depress the activity of epiphytic LAB, which explained the poor fermentation quality of control silage.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, the low terminal pH (<4.30) of the LAB-inoculated silages indicated satisfactory fermentation qualities. However, opposite results were obtained by Zhang et al [ 9 ], who reported that sufficient number of epiphytic LAB resulted in no effect of LAB inoculation on the fermentation quality of mulberry leaves. A possible explanation to this discrepancy could be the difference in DM content of mulberry leaves between two studies.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Aer air exposure in maize silage, Pinto et al 28,30 reported that the silos with natamycin alone and combined with L. buchneri showed the lowest pH and yeast values on day 1, while on day 3 the values were numerically changed in the natamycin additive group and on day 5 the yeast and pH were signicantly increased in the natamycin alone and control groups as compared to the combined natamycin and L. buchneri group. Some other chemical additives can also improve the aerobic stability of silage; Zhang et al 32 used propionic acid, L. plantarum and L. brevis to improve the aerobic stability. During seven days of air exposure for mulberry silage, the pH value and organic acid, yeast, and ammonia nitrogen concentrations were stable on days three.…”
Section: Discussionmentioning
confidence: 99%
“…Ensilage relies mainly on lactic acid bacteria (LAB) fermentation to convert water-soluble carbohydrates into organic acids, and LAB have been widely used as feed additives [14,15]. The combination of an acidic environment and the microbial fermentation process may synergistically degrade and/or produce new volatiles, and will often produce alcohols and acids which can make the fodder aroma acidic, fragrant, and alcoholic [14,15]. LAB can also be used in biodegrading and biotransforming terpenes in food fermentation and brewing [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%